2021
DOI: 10.1177/14604582211007536
|View full text |Cite
|
Sign up to set email alerts
|

The appropriateness of clinical decision support systems alerts in supporting clinical workflows: A systematic review

Abstract: A CDSS generates a high number of inappropriate alerts that interrupt the clinical workflow. As a result, clinicians silence, disable, or ignore alerts, thereby undermining patient safety. Therefore, the effectiveness and appropriateness of CDSS alerts need to be evaluated. A systematic review was carried out to identify the factors that affect CDSS alert appropriateness in supporting clinical workflow. Seven electronic databases (PubMed, Scopus, ACM, Science Direct, IEEE, Ovid Medline, and Ebscohost) were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 107 publications
(310 reference statements)
0
32
0
1
Order By: Relevance
“…121 Some studies (n = 10) mentioned 'alert fatigue' indicating that eCDS tools designed to support health professionals can increase the number of on-screen alerts, leading to a high chance of them being missed or ignored. 15,35,38,97,112,117,[122][123][124][125] None of these studies reported a decrease in consultation duration.…”
Section: Methods To Measure Consultation Durationmentioning
confidence: 95%
See 3 more Smart Citations
“…121 Some studies (n = 10) mentioned 'alert fatigue' indicating that eCDS tools designed to support health professionals can increase the number of on-screen alerts, leading to a high chance of them being missed or ignored. 15,35,38,97,112,117,[122][123][124][125] None of these studies reported a decrease in consultation duration.…”
Section: Methods To Measure Consultation Durationmentioning
confidence: 95%
“…98,104,111 Two articles that referred to the same core UK study, described capturing duration data from the practice IT system (Vision), based on the opening and closing of the EMR. 95,103 One USA study estimated consultation duration based on the reasons patients were attending -either for a 'shorter' visit, such as for acute care or follow-up, or for a 'longer' visit, such as for a general medical examination 96 , and two studies provided insu cient details of the methods used 92,112 .…”
Section: Methods To Measure Consultation Durationmentioning
confidence: 99%
See 2 more Smart Citations
“…A suboptimal design would lead to alerts being overridden, ignored or misinterpreted and can disrupt workflow, resulting in increases in consultation time, cognitive load and physical fatigue. 16 Successful development and implementation will depend on partnerships between clinicians, researchers, guideline developers and the medical software industry, so that any tools that are developed incorporate guidelines that are endorsed and trusted in a way that optimises usability in practice.…”
mentioning
confidence: 99%